The pro-apoptosis effects of Echinacea purpurea and Cannabis sativa extracts in human lung cancer cells through caspase-dependent pathway - Fatemeh Hosami; Azadeh Manayi; Vahid Salimi; Farshad Khodakhah; Mitra Nourbakhsh; Britt Nakstad; Masoumeh Tavakoli-Yaraki (BMC, 2021)
Abstract Background Considering the advantages of using medicinal herbs as supplementary treatments to sensitize conventional anti-cancer drugs, studying functional mechanisms and regulatory effects of Echinacea purpurea (as a non-cannabinoid plant) and Cannabis sativa (as a cannabinoid plant) are timely and required. The potential effects of such herbs on lung cancer cell growth, apoptosis, cell cycle distribution, cellular reactive oxygen species (ROS) level, caspase activity and their cannabinomimetic properties on the CB2 receptor are addressed in the current study. Methods The cytotoxic effect of both herb extracts on the growth of lung cancer cells (A549) was assessed using the MTT assay. The annexin-V-FITC staining and propidium iodide (PI) staining methods were applied for the detection of apoptosis and cell cycle distribution using flow cytometry. The cellular level of ROS was measured using 7'-dichlorofluorescin diacetate (DCFH-DA) as a fluorescent probe in flow cytometry. The caspase 3 activity was assessed using a colorimetric assay Kit. Results Echinacea purpurea (EP) root extract induced a considerable decrease in A549 viable cells, showing a time and dose-dependent response. The cell toxicity of EP was accompanied by induction of early apoptosis and cell accumulation at the sub G1 phase of the cell cycle. The elevation of cellular ROS level and caspase 3 activity indicate ROS-induced caspase-dependent apoptosis following the treatment of A549 cells by EP extract. The observed effects of EP extract on A549 growth and death were abrogated following blockage of CB2 using AM630, a specific antagonist of the CB2 receptor. Increasing concentrations of Cannabis sativa (CS) induced A549 cell death in a time-dependent manner, followed by induction of early apoptosis, cell cycle arrest at sub G1 phase, elevation of ROS level, and activation of caspase 3. The CB2 blockage caused attenuation of CS effects on A549 cell death which revealed consistency with the effects of EP extract on A549 cells. Conclusions The pro-apoptotic effects of EP and CS extracts on A549 cells and their possible regulatory role of CB2 activity might be attributed to metabolites of both herbs. These effects deserve receiving more attention as alternative anti-cancer agents. Graphical abstract